Contrastive Linguistics, Translation, and Parallel Corpora - Ebeling, Jarle (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis paper regards parallel corpora as suitable sources of data for investigating the differences and similarities between languages, and adopts the notion of translation equivalence as a methodology for contrastive analysis. It uses a bidirectional parallel corpus of Norwegian and English texts to examine the behaviour of presentative English there-constructions as well as the Norwegian equivalent det-constructions in original and translated English, and original and translated Norwegian respectively.